(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2017)
In order to reconstruct Europe’s past, the medieval chroniclers had to resort to a series of narrative texts of Greek and Roman origin, which were full of mythological elements, gods and heroes. In this paper we present the process of euhemerism used by these Christian clerics to doctrinally purify ancient history. The analysis of the universal chronicles written in the XII century reveals the construction of a narrative discourse based upon a rich language composed of nouns (fabula, mendacium), adjectives (fabulosus, fictus, ridiculus, mendax) and adverbs, with the purpose of discrediting the veracity of classical mythology.